1989
DOI: 10.1007/bf00375866
|View full text |Cite
|
Sign up to set email alerts
|

Differential transport requirements of HLA and H-2 class I glycoproteins

Abstract: Transport of human and mouse major histocompatibility complex class I glycoproteins has been examined in a transport deficient B-lymphoblastoid cell line X T-lymphoblastoid cell line (B-LCL X T-LCL) hybrid, 174 X CEM.T2 (T2). This cell line expresses no detectable endogenous HLA-B5 and reduced levels of HLA-A2 on its surface although these molecules are synthesized. In order to study this defect further, either HLA-Bw58 or HLA-B7 genomic clones were transfected into T2. Metabolic labeling and immune precipitat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
67
0

Year Published

1991
1991
2000
2000

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 135 publications
(74 citation statements)
references
References 45 publications
4
67
0
Order By: Relevance
“…H-2K b is expressed at high levels on the surface of the human TAP-deficient cell line T2, yet it is retained in the ER of the TAPdeficient mouse cell line RMA-S (24,25). This discrepant behavior of H-2K b in human and murine cells may reflect, in part, greater stabilization of K b complexed to human ␤ 2 m relative to K b complexed to murine ␤ 2 m. Therefore, we anticipated that H-2K b would also be expressed on the surface of human cells deficient in tapasin even though H-2K b is expressed at low levels (ϳ15% of wild-type levels) in tapasin knockout mice (A. G. Grandea, unpublished observations; and Ref.…”
Section: High-level Surface Expression Of H-2k B Class I Molecules Onmentioning
confidence: 99%
See 2 more Smart Citations
“…H-2K b is expressed at high levels on the surface of the human TAP-deficient cell line T2, yet it is retained in the ER of the TAPdeficient mouse cell line RMA-S (24,25). This discrepant behavior of H-2K b in human and murine cells may reflect, in part, greater stabilization of K b complexed to human ␤ 2 m relative to K b complexed to murine ␤ 2 m. Therefore, we anticipated that H-2K b would also be expressed on the surface of human cells deficient in tapasin even though H-2K b is expressed at low levels (ϳ15% of wild-type levels) in tapasin knockout mice (A. G. Grandea, unpublished observations; and Ref.…”
Section: High-level Surface Expression Of H-2k B Class I Molecules Onmentioning
confidence: 99%
“…Thus, murine class I molecules are expressed at high levels when transfected into human APC, whereas some HLA molecules require cotransfection of human ␤ 2 m to permit high levels of surface expression (24). However, in mutant APC there are certain anomalies that remain unexplained.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…T2 cells are derived from the parental T1 cell line, and have a large deletion in the MHC class II region including genes for the TAP1/2 and LMP2/7 products [30]. T2 cells transfected with H-2K b are designated T2K b [31]. All target cells were cultured in RPMI 1640 medium supplemented with 5% FCS, L-glutamine, penicillin and streptomycin.…”
Section: Methodsmentioning
confidence: 99%
“…The presence of these surface markers indicated that the cells cultured by our method fell within accepted criteria used to define purified, classical dendritic cells. Previous investigations have employed the T2 Ag-processing mutant [25,26] to identify CTL epitopes relevant for melanoma [see, for example, References 31,32] and ovarian carcinoma [21,22]. Expression of CD40, CD80 and CD86 costimulatory proteins, HLA-DR (class II), and ICAM-1, ICAM-3 and LFA-3 classical intercellular adhesion proteins, on the surface of DC-like cells prompted a comparative analysis between T2 and DC-like cells for their ability to elicit TNF-a release from anti-ovarian carcinoma CTL.…”
Section: Cytokine-induced Gelatin-adherent Cells Acquired Dc-like Chmentioning
confidence: 99%